Temperature dependences of the effective diffusion coefficients for two multicomponent gaseous systems containing air, hydrogen and some hydrocarbons - Zhavrin, Yu.I.; Moldabekova, M.S.; Asembaeva, M.K.; Fedorenko, O.V.; Mukamedenkyzy, V. (Recent Contributions to Physics, 2018)
Calculations of the exponents of temperature dependences of the effective diffusion coefficients (EDC) of gases for two multicomponent mixtures, which can be used for the combustion of gaseous fuels, are presented in the article.Transport properties of gases and its mixtures subject to the temperature effect are determined as the functional dependence. Temperature dependence of the EDC of components is presented in the semiempirical formula, which is similar to the power dependence of interdiffusion coefficients (IDC) on temperature. Given calculation schemes of the temperature dependences of EDC are carried out for the temperature range of 298 – 900 K and the atmospheric pressure.  The main sources of information for this work are the publication of a number of scientists, as well as the researches made by the authors of this article who developed tables of the recommended reference data of EDC for technically important diffusing multicomponent mixtures and certified them in the NRC MS of the State standard specification of USSRThe results allow revealing the mechanism of diffusion process in the complex gas mixtures under the temperature change and evaluating the transfer of each component and the total mass transport. The presented results can be used for the new reference data.
Keywords: diffusion, EDC, binary diffusion, baroeffect, masstransfer